2016
DOI: 10.1038/eye.2015.270
|View full text |Cite
|
Sign up to set email alerts
|

Persistent subfoveolar fluid following retinal detachment surgery: an SD-OCT guided study on the incidence, aetiological associations, and natural history

Abstract: Purpose To investigate the incidence and natural history of persistent subfoveolar fluid (PSF) following surgery for macular off rhegmatogenous retinal detachment and the effect of PSF on photoreceptor structure and final visual acuity. Methods Retrospective study of 61 cases with post-operative optical coherence tomography (OCT) performed within 12 weeks of surgery. Based on aetiology, cases were categorized into tractional retinal tears (TRT) group or atrophic round holes and dialyses (RHD) group to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 22 publications
(40 reference statements)
0
31
0
Order By: Relevance
“…In eyes with atrophic round retinal hole(s), a smaller volume of vitreous humor would tend to flow into the subretinal space because the age-related liquefaction of the vitreous body had not progressed. This will result in a slower progression of the detachment, and should lead to RRD eyes with atrophic round retinal hole(s) to have a systematic chronicity and the fluid current induced differences in the viscosity, protein, and cellular content of the subretinal fluid [29]. This would explain our observation of a higher incidence of SMF in the macula-off RRD treated by SB surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In eyes with atrophic round retinal hole(s), a smaller volume of vitreous humor would tend to flow into the subretinal space because the age-related liquefaction of the vitreous body had not progressed. This will result in a slower progression of the detachment, and should lead to RRD eyes with atrophic round retinal hole(s) to have a systematic chronicity and the fluid current induced differences in the viscosity, protein, and cellular content of the subretinal fluid [29]. This would explain our observation of a higher incidence of SMF in the macula-off RRD treated by SB surgery.…”
Section: Discussionmentioning
confidence: 99%
“…OCT imaging of the macular area can provide considerable help in explaining the mechanisms behind delayed functional recovery. Persistent «blebs», or «clefts» of SRF can be seen after macroscopically successful surgery for retinal detachment, including scleral buckling surgery [16]. The incidence of residual submacular fluid on the first postoperative OCT scan (4-6 weeks after surgery) for rhegmatogenous retinal detachment, according to various authors, varies from 15 to 90% [13,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the fluid may be of exudative origin or represent choroidal leakage [17,23]. However, most authors have concluded that the chronic course of detachment is a predisposing factor that leads to changes in viscosity, protein composition and cellularity of the SRF, which slows fluid absorption [16,24]. Tee et al [16], in comparing SRF absorption rates after RD surgery in patients with atrophic and tractional tears, discovered that chronic detachments associated with atrophic tears required a three times greater period for SRF resorption when compared with acute detachments associated with tractional tears [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It means that delayed residual subfoveal fluid resorption is a common phenomenon in clinically successful surgery. Although most cases resolve with observation, long-standing submacular fluid can damage photoreceptors, cause permanent visual loss, trigger retinal thinning, and possibly contribute to macular hole formation [7, 8].…”
Section: Introductionmentioning
confidence: 99%